EFEKTIVITAS KEBIJAKAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Muhammad Ilyas; Andi Purbaya; Maria Ulfa; Moch. Bazarul Ausar (Program Studi Pendidikan Agama Islam, 2024)
The head of the madrasa is the leader of the institution he or she leads. The progress and development of the institution is the task and responsibility of the madrasa head. A leader is someone who carries out activities to influence others in the environment in a specific situation, so that others are willing to work with a sense of responsibility in order to achieve the set goals. The success of the madrasa head in implementing policy programs is assumed to be the result of the hard work and skill of the madrasa head in creating operational policies to improve the professionalism of teachers. This research aims to examine the implementation of the Satmingkal policy (four times a week) in improving the professional competence of teachers in mastering the subjects taught and in developing teaching materials at MTs SA Al-Alawiyah Karangpring, Sukorambi, Jember. The research method used is a qualitative method with a phenomenological research type. This is a qualitative study with data sources from the school principal, vice-principal of curriculum, and teachers at MTs SA Al-Alawiyah Karangpring, Sukorambi, Jember. Data collection methods include interviews, observation, and documentation related to the Satmingkal policy and the improvement of teacher professionalism at MTs SA Al-Alawiyah Karangpring, Sukorambi, Jember. The data analysis technique used in this study is triangulation of techniques and triangulation of sources. Based on the research results, the implementation of the